High structural quality InGaN/GaN multiple quantum well solar cells. Issue 12 (31st August 2015) - Dogmus, Ezgi; Zegaoui, Malek; Largeau, Ludovic; Tchernycheva, Maria; Neplokh, Vladimir; Weiszer, Saskia; Schuster, Fabian; Stutzmann, Martin; Foldyna, Martin; Medjdoub, Farid
Abstract: In this paper, we report on high structural quality of above 15% indium content InGaN/GaN multiple quantum well (MQW) structures with high equivalent thickness for solar cell applications. The structural and optical characterizations revealed fully strained 25 pairs of InGaN/GaN MQW solar cells with 24% indium content which shows extended spectral response up to 530 nm. In particular, defect density of the active region of In0.15 Ga0.85 N/GaN MQW solar cell has been assessed in top view electron beam induced current (EBIC) analysis. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)